Conformity of Islamic Banks with AAOIFI Standards for General Presentation and Disclosure in Turkey and Bahrain - Yusuf Avşar; Ozan Özdemir (Türkiye İslam İktisadı Dergisi)
Islamic (participation) banks in Turkey are required to apply international accounting standards in their accounting and reporting practices, while their counterparts in Bahrain apply the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) standards. The main objective of this paper is to reveal the relation between Islamic and international accounting standards, discussed in previous studies, by comparing the compliance to AAOIFI accounting standards by Islamic banks in both Turkey and Bahrain. The source of information in this study is secondary data provided in the annual reports of the Islamic banks in Turkey and Bahrain for the year 2017. In order to measure compliance, an unweighted disclosure index was used. The outcomes of this study show that, since AAOIFI accounting standards are compulsory in Bahrain, the level of compliance with AAOIFI standards in relation to general presentation and disclosure in the financial statements of Islamic banks in Turkey is lower than the compliance achieved by their counterparts in Bahrain. Due to the average compliance level achieved by Islamic banks (using the unweighted disclosure index) in Turkey (54.6%), and since all banks in Turkey apply international financial reporting standards and international accounting standards, it is found that there is a relation between AAOIFI and International Accounting Standards Board standards even though they are different. Surprisingly, in the case of Bahrain’s Islamic banks, the standard deviation of the total compliance score is 8.66, which indicates an important difference among the Islamic banks in Bahrain in this regard. It is also found that the current practices of participation banks in Turkey do not adequately meet the financial statements and disclosure standards in accordance with the AAOIFI.